INTEGRATED SEDIMENTOLOGICAL AND SEISMIC ANALYSIS OF A CARBONATE RESERVOIR IN CENTRAL LUCONIA, MALAYSIA - MAKHANKOVA, ADELIA (2020)
The porosity-permeability architecture of carbonate buildups in Central Luconia, Malaysia still remain ambiguous. The evolution of isolated carbonate buildups rely on multiple forcing factors, including tectonics and eustatic fluctuations. These parameters control the developmental phases of carbonate buildups such as initiation, growth and termination stages, and give insights into other morphologic patterns such as backstepping and exposure events. The current study shows the evolution of a Middle to Late Miocene isolated carbonate buildup of Central Luconia in the southern South China Sea, and describes it from large-scale to very fine detail (km to mm) utilizing newly acquired (2016) 3D seismic data along with core and thin sections.